Anesthesia Management in A Newborn Baby with Tracheoesophageal Fistula: A Case Report - Anak Agung Gde Agung Wibisana; Tjokorda Gde Agung Senapathi; I Putu Kurniyanta (HM Publisher, 2023)
Background: In infants with esophageal atresia/tracheoesophageal fistula, excessive salivation, coughing, choking, cyanosis, and regurgitation associated with attempts to eat may be seen, as well as aspiration of gastric contents. Thus difficulties encountered during anesthetic management include ineffective ventilation due to an endotracheal tube placed in the fistula, massive gastric dilatation, preexisting severe lung disease from aspiration of gastric contents and/or respiratory distress syndrome of prematurity, and associated anomalies, especially cardiac. This study aimed to discuss the anesthetic management of neonates with tracheoesophageal fistula. Case presentation: The patient was a 12-day-old baby girl with type C tracheoesophageal fistula. Anesthesia was performed using general anesthesia. The procedure lasts 3 hours 15 minutes. The patient underwent closure of the esophageal fistula, repair of the trachea in the distal part of the tracheoesophageal fistula, and performed end-to-end anastomosis proximal and distal esophagus. Postoperatively the patient was treated at the neonatal intensive care unit on a ventilator and given a combination of opioid and non-opioid analgesics. Conclusion: The key to successful anesthetic management in the operation of a patient with a tracheoesophageal fistula is airway management, where the ETT must be properly placed on the trachea and try not to get the ETT into the fistula.